Exploring the relationship between exchange rate and trade balance in Somalia. A Bayesian VAR and other econometrics model approach - Mohamud Hussein Mohamud; Fartun Ahmed Mohamud (Cogent Economics & Finance, 2025)
This study explores the relationship between Somalia’s exchange rate and trade balance, considering additional factors such as inflation, the trade-to-GDP ratio, imports, and foreign direct investment (FDI). Using secondary data from the World Bank covering 1990 to 2022, the analysis applies three econometric methods. The Bayesian Vector Autoregression (BVAR) model shows a short-run relationship between the exchange rate and trade balance. The Fully Modified Ordinary Least Squares (FMOLS) results indicate that trade balance and inflation have a long-term negative impact on the exchange rate, while FDI positively influences it in the long run. The Ordinary Least Squares (OLS) regression confirms these findings, showing that increases in trade balance and inflation lead to currency depreciation. These results suggest that Somali policymakers should develop sustainable trade policies that improve the trade balance, increase the trade-to-GDP ratio, and attract more FDI to stabilize the exchange rate.